Perancangan UI/UX Aplikasi E-Arsip Data Debitur Pada PT. Bank Rakyat Indonesia - Cerah, Muhamad; Alfresi, Aminullah Imal (MDP Student Conference, 2024)
This research aims to design the user interface (UI/UX) of the Debtor Data E-Archive application by applying the Design Thinking method at PT. Bank Rakyat Indonesia, especially Bank BRI KCP Ampera. This was done because the previous archive system called BRIMEN was deemed not very effective and efficient because the archive data input process still involved microsoft excel so this system was less flexible when operated by employees. By optimizing the user interface through a Design Thinking approach, it is hoped that the designed application can provide a better user experience and support operational efficiency in managing debtor data archives. The stages in the Design Thinking method include the process of empathize, define, ideate, prototype, and testing. The results of this research are the UI/UX design of the E-Archive Debtor Data application which has gone through the final stages of testing and received positive responses and significant scores from potential users, indicating that this system has a positive contribution to improving the quality of Bank Rakyat Indonesia's customer debtor data archive services.